RESEARCH OF EUPHEMISMS IN WORLD LINGUISTICS. THE CONCEPT OF WOMEN IN EVEMISMS (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the essence of the phenomenon of euphemism in world linguistic culture, the definitions given by scientists, and the study of euphemisms by world linguists are given. Euphemisms representing the concept of woman are also discussed.